SAT0727-HPR CHANGES IN ACHILLES TENDON STIFFNESS IN GOUT MEASURED BY ELASTOGRAPHY – A PRELIMINARY STUDY. (June 2019) - Otter, Simon; Payne, Catherine; Jones, Anna-Marie; Webborn, Nick; Watt, Peter
Abstract : Background: In addition to acute attacks of severe joint pain and swelling, chronic gout has been associated with weaker foot/leg muscles, altered gait patterns and on-going foot pain. Inflammation associated with gout may change tissue elasticity and ultrasound imaging (US) utilising elastography is a non-invasive method of quantifying these changes in tendon stiffness and elastography findings have not previously been reported in individuals with gout. Objectives: To determine differences in Achilles tendon stiffness in people with chronic gout compared to controls (non gout) Methods: A cross sectional study comparing people with gout according to 2015 ACR/EULAR criteria and age/sex matched controls. Clinical and demographic data were collated and US imaging used to determine tendon thickness, presence of gouty tophi and/or aggregates and levels of angiogenesis. Previously validated protocols for conventional US imaging [1] and shear wave elastography [2] were used. Prior to data collection, intra-observer error was good (ICC (2) 0.69 (95%CI 0.62-0.89)). Ten elastography measures were taken along a longitudinal section of the mid-point of the Achilles tendon bilaterally. Data were summarised using descriptive statistics and a repeated measures ANCOVA was used to compare elastography outcomes between the two groups for the left and right foot separately after accounting for Body Mass Index (BMI). Results: A total of 14 people with gout and 13 age/sex matched control subjects participated. Table 1 displays clinical and demographic data. A small proportion of those with gout presented with intra-tendon aggregates and/or intra-tendon tophi in one or both tendons n=7 (27%) for both). There was no significant difference in tendon thickness between groups, neo-vascularity was present in n=3 (21%) gout participants. Elastography findings (table 2 ) demonstrated significantly reduced tendon stiffness in those with gout compared to controls. Conclusion: Subjects with chronic gout show reduced Achilles tendon stiffness compared to controls. From a clinical standpoint, our findings were similar to elastography measurements in otherwise healthy subjects with Achilles tendinopathy and who did not have gout [3]. References: [1] Carroll M, Dalbeth N, Allen B, et al. Ultrasound Characteristics of the Achilles Tendon in Tophaceous Gout: A Comparison with Age- and Sex-matched Controls. J Rheumatol. 2017 44(10):1487-1492. [2] Payne C, Watt P, Cercignani M, Webborn N. Reproducibility of shear wave elastography measures of the Achilles tendon. Skeletal Radiol. 2017 17 2846-8. [3] Payne C 2018 Clinical Applications of shear wave elastography to Achilles tendon imaging and monitoring of a rehabilitation protocol for Achilles tendonopathy PhD Thesis, University of Brighton Disclosure of Interests: None declared